Antireflective Nanocomposite Based Coating on Crystalline Silicon Solar Cells for Building-Integrated Photovoltaic Systems. (29th May 2013) - Gangopadhyay, Utpal; Jana, Sukhendu; Das, Sayan; Garain, Sutapa; Ray, Soma
Abstract : Building-integrated photovoltaic (BIPV) systems represent an interesting, alternative approach for increasing the available area for electricity production and potentially for further reducing the cost of solar electricity. In BIPV systems, the visual impression of a solar module becomes important, including its color. However, the range of solar cell colours and shapes currently on offer to architects and BIPV system designers is still very limited, and this is a barrier to the widespread use of PV modules as a constructional "material." The color of a solar module is determined by the color of the cells in the module, which is given by the antireflection coating (ARC). However, access to efficient, but differently colored, solar cells is important for the further development of BIPV systems. In this paper, we have used Diamond-like nanocomposite layer as an Antireflective Nanocomposite based (ARNAB) coating material for crystalline silicon solar cell, and the impact of varying the color of an ARC upon the optical characteristics and efficiency of a solar cell is investigated. In addition to a comparison of the optical characteristics of such solar cells, the effect of using colored ARCs on solar cell efficiency is quantified using the solar cell modeling tool PC1D.